School Based Iron Supplementation to Reduce Anemia - Anggaraeni, Lina; Luh Ayu Purnami; Cindy Meilinda Sari (HealthCare Nursing Journal, 2025)
Anemia is a common health issue affecting adolescent girls, particularly in countries with low to middle income. One of the leading causes is iron deficiency, often due to insufficient dietary intake and poor compliance with supplementation programs, even when national initiatives such as Weekly Iron Folic Acid Supplementation (WIFAS) are in place. This study aimed to assess the impact of a comprehensive intervention conducted in schools on improving hemoglobin levels, knowledge, and adherence to iron supplementation among teenage girls. A quasi-experimental study using a pre-post control group design was carried out over twelve weeks in two public senior high schools located in Bali Mandara, Buleleng, Indonesia. A total of 200 female students aged between 15 and 17 years were randomly assigned into intervention and control groups. The intervention strategy included weekly supervised intake of iron tablets, biweekly educational sessions on anemia, peer support mechanisms, and involvement of parents in the program. The evaluation focused on changes in hemoglobin levels, knowledge related to anemia, and records of supplementation adherence. The results revealed notable improvements in all three indicators among students in the intervention group. Specifically, the program contributed to better awareness, more consistent tablet consumption, and an overall reduction in anemia prevalence. These findings suggest that combining education, direct supervision, and family participation within a school-based framework can effectively support anemia prevention and improve adolescent health outcomes.